2017
DOI: 10.18632/oncotarget.15193
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin promotes the bacteriostatic activity of lysozyme on S. aureus in mammary glands and neutrophilic granulocytes in mice

Abstract: Staphylococcus aureus causes mastitis as a result of community-acquired or nosocomial infections. Lysozyme (LYSO) is an enzyme that is upregulated in many organisms during the innate immune response against infection by bacterial pathogens. Baicalin is a bioactive flavonoid that can bind to enzymes, often to potentiate their effect. Here we tested the effects of baicalin on the activity of LYSO using the S. aureus mastitis mouse model and neutrophilic granulocyte model of S. aureus infection. In our experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…Baicalin is a flavone glucuronide with extensive pharmacological effects including antibacterial, [61] antiallergic, [62] and anti-inflammatory [63] effects. Despite all these pharmacological effects, its low aqueous solubility limited its clinical application.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…Baicalin is a flavone glucuronide with extensive pharmacological effects including antibacterial, [61] antiallergic, [62] and anti-inflammatory [63] effects. Despite all these pharmacological effects, its low aqueous solubility limited its clinical application.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…Baicalin (5,6-dihydroxy-7-O-glucuronide flavone, BA) is the main effective constituent isolated from the roots of the Chinese medical herb Scutellaria baicalensis Georgi, which is widely used in pneumonia, hepatitis, atherosclerosis [ 8 ], and other conditions. Recent studies have indicated that BA has many pharmacological activities, like anti-inflammation [ 9 ], antioxidative stress [ 10 ], neuroprotective [ 11 ], and antibacterial [ 12 ]. Increasing researches have showed that BA has a protective effect on ALI induced by LPS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme functions by cleaving the ÎČ-1,4-glycosidic bond between N-acetylmuramic acid and N-acetylglucosamine residues of the bacterial peptidoglycan, causing a loss of cellular membrane integrity and cell lysis [1, 10]. Lysozyme was reported to be more effective against gram-positive bacteria [16, 17, 18], and it may also indirectly affect several gram-negative bacterial species [12, 19]. Previous studies revealed that lysozyme promotes the beneficial microbe community and reduces detrimental microbes within gut microbial communities [11, 20].…”
Section: Introductionmentioning
confidence: 99%